A paradox: Midwives' Experiences of Attending a Birth Resulting in Maternal Death in a Ghanaian Context - Susanna Aba Abraham; Gifty Osei Berchie; Andrew Adjei Druye; Charles Agyemang Prempeh; Christiana Okantey; Kweku Agyei Ayensu (Mashhad University of Medical Sciences, 2020)
Background & aim: In a lower-middle income country, such as Ghana, maternal death still occurs even in case of providing skilled perinatal care. The impact of maternal death on the family, community, and society has been largely studied. However, its implications for midwifery practice in Ghana has not been extensively investigated. The purpose of this study was to explore the experiences of midwives whose clients died during the peripartum period and unearth the influence of their experiences on their personal lives and practices as midwife. Methods: The present study adopted a descriptive exploratory approach. Purposive and snowball sampling were employed to recruit six midwives attending the women who died during the peripartum period. The experiences of midwives were uncovered using in-depth interviews. Data analysis was conducted using Colaizzi's phenomenological method as a frame of reference. Rigor was maintained through member checking and prolonged engagement. Results: Four main themes emerged from the data, including conceptualizing maternal death, midwives initial reaction to maternal death, perceived preparedness to manage maternal death, and building resilience (blurring the memory). There was minimal institutional support for the midwives when maternal death occurred. The participants used various coping strategies to rebuild their self-confidence and professional confidence. Conclusion: Midwives attending women who die during the peripartum period suffer emotionally and psychologically. The implications of these experiences in the midwifery profession are enormous. Supportive strategies should be institutionalized to achieve the complete recovery of attending midwives and provide experiential training of the entire midwifery staff.